Comparative Study of the Antimicrobial Effects of Tungsten Nanoparticles and Tungsten Nanocomposite Fibres on Hospital Acquired Bacterial and Viral Pathogens - Rupy Kaur Matharu; Lena Ciric; Guogang Ren; Mohan Edirisinghe (Nanomaterials, 2020)
A significant proportion of patients acquire hospital associated infections as a result of care within the NHS each year. Numerous antimicrobial strategies, such as antibiotics and surface modifications to medical facilities and instruments, have been devised in an attempt to reduce the incidence of nosocomial infections, but most have been proven unsuccessful and unsustainable due to antibiotic resistance. Therefore, the need to discover novel materials that can combat pathogenic microorganisms is ongoing. Novel technologies, such as the potential use of nanomaterials and nanocomposites, hold promise for reducing these infections in the fight against antimicrobial resistance. In this study, the antimicrobial activity of tungsten, tungsten carbide and tungsten oxide nanoparticles were tested against Escherichia coli, Staphylococcus aureus and bacteriophage T4 (DNA virus). The most potent nanoparticles, tungsten oxide, were incorporated into polymeric fibres using pressurised gyration and characterised using scanning electron microscopy and energy dispersive X-ray spectroscopy. The antimicrobial activity of tungsten oxide/polymer nanocomposite fibres was also studied. The results suggest the materials in this study promote mediation of the inhibition of microbial growth in suspension.